EFEKTIVITAS PELAKSANAAN PROGRAM PEMBANGUNAN INFRASTRUKTUR DESA DIDESA BAWO KECAMATAN TAGULANDANG UTARA KABUPATEN KEPULAUAN SITARO - Mangerongkonda, Yulani; ROMPAS, WELSON; MAMBO, RULLY (Sam Ratulangi University, 2019)
This research was conducted to find out effective it is implementation of development programs infrastructure village Bawo Kecamatan Tagulandang Utara Kabupaten Kepulauan SITARO. Bawo Village government increases infrastructure through the construction of infrastructure which prioritizes the basic rights of the community and the availabilility of infrastructure and quality as efforts to support accelerated development and enhancement passion for economic activity. And the problem found in the village of Bawo is how effectiveness of implementing infrastructure development programs in he village of Bawo this research aims to find out how effective it is implementation of infrastructure development in the village Bawo. The method used this study Is a qualitatitive method for later, fpr later analysis data collection is done by interview directly to the research informant who have determined by qualitative methods, to see how effective it is implementation of infrastructure development programs in the village Bawo Kecamatan Tagulandang Utara Kabupaten Kepulauan SITARO. Research use two indicators namely : the amount of result that can be issued meaning that the results are in the form of quantity or physical form the organization, program or activity. The intended result can be seen from Ratio (antara masukan) Input (dengan keluaran) output level of satisfaction obtained. Meaning in this effectiveness can quantitative ( based on numbers oe lots) and can be qualitative ( based on quality)Keywords : Effectiveness, Development, Infrastructure